The Comparative Analysis of National Policies for Research and Education Regarding Usage of Generative AI in Japan, the USA and the UK - Nagayuki Saito (International Telecommunications Society (ITS), 2024)
Generative AI is rapidly proliferating in society and its impact extends to education and research. This study analyzes the impact of generative artificial intelligence (AI) in the field of education and research from an international perspective and compares it with Japan's educational policies. The findings revealed that the U.S. policies emphasize the personalization and adaptability of AI in education, whereas the U.K. has specified concrete measures against the negative aspects of generative AI, particularly its misuse. In contrast, the Japanese policy has adopted a strategy of delineating issues in education and research to support individual educational institutions in their policymaking regarding AI.
Keywords: 330; Generative AI; Research and Education; Educational Policies